COMPARATIVE STUDY ON THE LEADERSHIP STYLES OF ICE HOCKEY ACADEMY COACHES - Maria Daniela MACRA-OȘORHEAN; Hunor Flavius CRIȘAN; Paul Ovidiu RADU (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2023)
Leadership style is an essential component of the effectiveness of the coach’s work. There are three styles of coaches generally accepted in sports: dictatorial, democratic and negligent. Each of these styles has its own advantages and disadvantages, which is why it is important to understand each of them. Purpose of the study. The purpose of this research was to determine, by means of an applied questionnaire, to what extent coaches use leadership styles and their impact within a sports organization. Methods and means. To carry out this study, the questionnaire-based survey method was used - The Coaches’ Interpersonal Style Questionnaire (Pulido et al., 2018). It included 10 questions with reference to the leadership style of the coaches. The questionnaire measured 3 forms of leadership style – democratic, authoritarian and negligent. The collected data were measured using a 5-item Likert scale represented by the numbers 1 – never, and 5 – frequently/always. Results. The comparative graphic clearly shows an absolute dominance of the democratic style in each center, in the dictatorial style there is a predominantly significant difference between clubs, and the negligent style is used less often or never. Conclusions. In general, the coaches have understood the modern trends and that is why the democratic leadership style prevails, managing to involve even very young athletes in decision-making, which also implies responsibility for both parties.